How hierarchical structures may influence the way that we think - Loehrlein, Aaron (Proceedings of the American Society for Information Science and Technology, 2010)
This paper presents experimental results showing that a user's interaction with hierarchical classification may affect the user's conceptual structures. After performing a directed browsing task using a hierarchical classificatory structure, subjects rated as more important the concepts that were organized in the top tier of the hierarchy. The results of the study suggest that, although subjects adapted their conceptual structures to the hierarchical structure in some conditions, these effects depend not only on the structure, but on the specific concepts that appear in the structure.